National Microbiological Laboratory Reporting Service - Bulletin 10. 6-19 May 1977 - whole issue - No author listed, (Communicable Diseases Intelligence, 1977)
Whole-issue pdf, comprising: Article Typhoid outbreak in Melbourne. [see also Bulletins 9 and 11] Q fever . [Abbattoir in Forbes, N.S.W.] [See also Bulletins 7 and 9] Herpes simplex encephalitis. [Melbourne, Vic] Gastroenteritis outbreak in nursery (further report) [previous report in Bulletin 8] Advances in viral hepatitis. [A report of the WHO Expert Committee on Viral Hepatitis] National Microbiological Laboratory Reporting Service - Period 10 6-19 May 1977